1993
DOI: 10.1007/bf02460888
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion driven instability in an inhomogeneous domain

Abstract: Diffusion driven instability in reaction-diffusion systems has been proposed as a mechanism for pattern formation in numerous embryological and ecological contexts. However, the possible effects of environmental inhomogeneities has received relatively little attention. We consider a general two species reaction~diffusion model in one space dimension, with one diffusion coefficient a step function of the spatial coordinate. We derive the dispersion relation and the solution of the linearized system. We apply ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 17 publications
3
56
0
Order By: Relevance
“…Thus, for aggregation to form, we require this state to be unstable to spatially inhomogeneous perturbations (Benson et al, 1993), i.e. the maximum real part of the eigenvalues to be greater than zero.…”
Section: Of 36mentioning
confidence: 99%
“…Thus, for aggregation to form, we require this state to be unstable to spatially inhomogeneous perturbations (Benson et al, 1993), i.e. the maximum real part of the eigenvalues to be greater than zero.…”
Section: Of 36mentioning
confidence: 99%
“…Such a system has been studied in one dimension by one of us [11], and it has been shown that the dispersion relation does not admit an analytic solution, even in the simple case of a step-like variation of the diffusion constant and zero-flux external conditions. In general, the Laplacian should be replaced by ∇ · (D(x, y)∇u).…”
Section: The Modelmentioning
confidence: 99%
“…Former studies in one dimension of a Schakenberg system with a step-like variation of the diffusion constants [11] show that there are three types of patterns, depending on the value of the ratio D o /D i . Roughly speaking, when this ratio is large, isolated patterns (type A) are obtained in each region, and there is a discontinuity at the border.…”
Section: Numerical Calculationsmentioning
confidence: 99%
“…However, as experimental evidence suggests, some embryological systems may exhibit environmental inhomogeneities. The form of Turing patterns in such cases was analysed by Benson et al (1993). They considered a two-species reaction-diffusion system where the dispersal rate of one species varied in a simple step-wise manner, and discussed its application to the development of cartilage pattern in embryonic chick limb.…”
Section: Continuum Models For Pattern Formationmentioning
confidence: 99%